AKIBAT HUKUM TERHADAP PIHAK YANG TIDAK BERITIKAD BAIK DALAM PROSES JUAL BELI - Sukindar, Norma dan (Universitas 17 Agustus 1945 Samarinda, 2020)
Buying and selling is an activity carried out by two or more people to produce a mutual agreement, but there is often a sale and purchase which causes various problems. The existence of buying and selling with object agreements contain hidden defects. The situation is actually known consciously by the seller, but did not inform the buyer about it, so the buyer feels disadvantaged. Such events occur because of bad intentions or dishonest attitudes about information and the condition of an item. As a result of dishonest acts, the interests of one party have been violated. The problem raised in this paper is what the legal consequences are for parties who have no good intentions in the buying and selling process and what are the factors causing the parties to set aside good faith in the buying and selling process.This type of research is normative juridical research, library research with the problem approach used in writing this thesis is the statute approach.The results showed that with the enactment of legislation governing the buying and selling process of parties who do not have good intentions will cause legal consequences, namely the agreement becomes invalid and null and void and compensates for damages. But the reality on the ground, that the replacement of losses can be done if the parties agree. The factor causing the parties to set aside good faith in the buying and selling process is the lack of careful buyer or consumer to look for more detailed information related to the items they want to buy. While the seller or business actor, because of the opportunity to have bad intentions, in addition to that because of dishonesty.